Simulation of Electromagnetic Field of a Powerful Electrical Machine - D. I. Hvalin; O. H. Kensytskyi; K. O. Kobzar (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
With the aid of mathematical and physical simulation the electromagnetic field distributions in the end zone of a powerful turbogenerator has been obtained. On the basis of the comparison of the axial component of the magnetic induction on the surface of the extreme package of the stator core of the large-scale physical and mathematical models with the data of the field experiment, conclusions are drawn about the reliability of the results obtained. The data of the simulation and the field experiment correspond to the same turbogenerator, which makes it possible to evaluate the correctness of the construction of the mathematical model. It is shown that physical modeling makes it possible to evaluate the regularities of the distribution of the electromagnetic field (without obtaining accurate quantitative indicators) and can be used for qualitative comparison of the effectiveness of various design solutions of the end zone of the stator. However, such models have not become widely used, since numerous studies are required to form meaningful and sufficiently detailed conclusions about the parameters and characteristics of the object, the design of the end zone of high-power generators is complex, and the calculation of three-dimensional models is time-consuming and even with modern computer technology is associated with a number of simplifying factors. In mathematical modeling, a sequential logical transition is applied from a simple model of the central part of the machine to a more complex model of the end zone using preliminary results, which makes it possible to obtain data on the distribution of the electromagnetic field in complex areas. With the help of specialized software, a model has been created that is quite flexible in terms of modifying individual components, characterized by accessibility, visibility and unlimited possibilities for experimentation, including predicting situations that have not previously occurred or can give unpredictable results.